Measuring construction for social, economic and environmental assessment - Ilhan, Bahriye; Yobaş, Banu (Emerald, 2019)
Purpose The purpose of this paper is to examine the issues that should be considered for a better gauge of the construction industry and built environment and to propose a set of indicators for measuring the social, economic and environmental value of construction. Design/methodology/approach The indicators proposed in this study use Pearce’s schema, which presents a framework to evaluate the socio-economic value of construction and its contribution to sustainable development. After analysing the problems faced by the industry, solutions are raised and finally indicators for each pillar of Pearce’s schema are established through a literature review. Since the proposed indicators can be used for cross-country analysis, these comparisons are also presented as graphs including only those countries for which valid national data could be sourced from OECD databases. Findings The issues, suggestions and indicators related to each concern about the main domains of the schema are addressed through the related literature and supported by available statistical data. Originality/value Although previous studies have drawn attention to measures for better evaluation of the construction industry and the built environment, this study, distinctively, presents an integrated approach in order to gauge the true value and impacts of construction in a more comprehensive way. The work’s contribution to the body of knowledge is in revealing the hidden input and impact of construction on sustainable development by determining the barriers to this and their solutions, in addition to the proposal of relevant indicators.
Keywords: Built environment; Engineering; Business and economics; Economics; FOS: Political science; Construction engineering; Pillar; Sustainable Construction and Green Building; Sustainability Assessment and Impact Evaluation; Schema (genetic algorithms); Engineering; Sociology; Sustainable development; International construction; Political science; Built environment; International construction; Sustainable development; Construction industry; Approach; Pearce's schema; Ecology; Building Environmental Assessment; Social science; FOS: Sociology; Sustainable Construction; Sustainability; Physical Sciences; Urban Sustainability Indicators; Environmental economics; Structural engineering; FOS: Law; Management, Monitoring, Policy and Law; Qualitative research; Machine learning; Biology; Approach; Originality; Business and economics; Building and Construction; Sustainability Indicators; Measurement and Evaluation of Sustainable Development; Construction industry; Computer science; Pearce's schema; Management science; FOS: Biological sciences; Environmental Science; Sustainability Assessment; Law